2000
DOI: 10.1007/s001140050752
|View full text |Cite
|
Sign up to set email alerts
|

“You are what you eat”: Diet modifies cuticular hydrocarbons and nestmate recognition in the Argentine ant, Linepithema humile

Abstract: Nestmate recognition plays a key role in the behavior and evolution of social insects. We demonstrated that hydrocarbons are the chemical cues used in Argentine ant, Linepithema humile, nestmate recognition, and that these hydrocarbons can be acquired from insect prey. Consequently, Argentine ant cuticular hydrocarbon patterns reveal the same hydrocarbons present in their diet. Diet alters both the recognition cues present on the cuticular surface and the response of nestmates to this new colony odor, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
249
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(267 citation statements)
references
References 31 publications
14
249
4
Order By: Relevance
“…At least for this study, the variation in behaviour seems not to be substantially spatially or genetically determined (unless the neutral variation detected by microsatellites is not representative of the variation encoding aggressive behaviour). Rather, the behavioural variation observed might depend on (i) the context as suggested, for example, for L. austriacus (Steiner et al 2007), or (ii) the experience of workers in previous encounters with non-nestmates (Van Wilgenburg et al 2010), or (iii) environmentally derived cuticular hydrocarbon cues (Liang & Silverman 2000). Furthermore, recent studies regarding correlations between behaviour and, for example, spatial distance revealed contrasting results: in some cases, spatial distance and aggressive behaviour were correlated (Pirk et al 2001; Benedek & Kobori 2014; Frizzi et al 2015; Fournier et al 2016), while in others, no correlation was observed (Langen et al 2000; van Wilgenburg 2007; Martin et al 2012), corroborating the general need for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…At least for this study, the variation in behaviour seems not to be substantially spatially or genetically determined (unless the neutral variation detected by microsatellites is not representative of the variation encoding aggressive behaviour). Rather, the behavioural variation observed might depend on (i) the context as suggested, for example, for L. austriacus (Steiner et al 2007), or (ii) the experience of workers in previous encounters with non-nestmates (Van Wilgenburg et al 2010), or (iii) environmentally derived cuticular hydrocarbon cues (Liang & Silverman 2000). Furthermore, recent studies regarding correlations between behaviour and, for example, spatial distance revealed contrasting results: in some cases, spatial distance and aggressive behaviour were correlated (Pirk et al 2001; Benedek & Kobori 2014; Frizzi et al 2015; Fournier et al 2016), while in others, no correlation was observed (Langen et al 2000; van Wilgenburg 2007; Martin et al 2012), corroborating the general need for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our preliminary analysis indicated that both hydrocarbons were readily acquired by Argentine ants. For S. longipalpa, we selected 15,19-dimethylheptatriacontane present in S. longipalpa at 19.0% and acquired by Argentine ants from S. longipalpa prey (Liang and Silverman, 2000;Liang et al, 2001). To compare changes in individual hydrocarbon levels (average level on day 140 vs. average level on day 0), we used one of two types of t-tests, depending on the equality of variances.…”
Section: Methodsmentioning
confidence: 99%
“…The signals used in nestmate recognition are primarily under genetic control; however, exogenous cues derived from nest materials (Gamboa et al, 1986;Stuart, 1987) or diet (Jutsum et al, 1979;Obin and Vander Meer, 1988;Le Moli et al, 1992;Liang and Silverman, 2000) may also play a role. Cuticular hydrocarbons have long been considered important mediators of nestmate recognition in ants (Vander Meer and Morel, 1998), with recent evidence supporting a direct role (Lahav et al, 1999;Liang and Silverman, 2000). However, the relative contribution of heritable and environmentally derived cues, including hydrocarbons, to the recognition profile is not known.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations